MANUVER DAN GAYA POLITIK GIBRAN DI PILPRES 2024 - Hamdi, Saipul (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This article examines Gibran Rakabuming Raka's political approach in the 2024 presidential election campaign. Gibran was nominated as Vice President by the Advanced Indonesia Coalition (KIM), along with Prabowo Subianto. This article focuses on Gibran's political moves, the debate over the Constitutional Court judgment, and his motives for joining the Prabowo side. This study used a qualitative method employing a desk study approach. The findings indicate that Gibran's maneuvering was observed when he met Prabowo at Omah Semar Angkringan in Solo. Accepting Prabowo's proposal was due to his ability to persuade Jokowi, and he was the only candidate that explicitly proposed Gibran as vice president. Accepting Prabowo's proposal was due to his ability to persuade Jokowi, and he was the only contender that explicitly proposed Gibran as vice president. Prabowo's choice is also more sensible than Ganjar's in terms of political calculations, such as voter distribution in areas where Prabowo is more equally dispersed. Prabowo has a high level of electability in West Java, whereas Gibran is in Central Java. Another finding of the study is that Gibran's political style shifted during the Presidential Election campaign, including shorter speech, very powerful media branding, and the use of manga logos, which are popular among young people.